Steroid Therapy in the Management of Sudden Sensorineural Hearing Loss: A Nonrandomized Clinical Trial - Swaminathan, Gowri; Ramalingam, Ravi; Kombupalayam Kumarappa Gounder, Ramalingam (Annals of Otology and Neurotology, 2019)
Objective The aim of this study was to compare the effectiveness of intratympanic (IT) steroid therapy and combined intravenous-cum-intratympanic (IVIT) steroid therapy in the management of sudden sensorineural hearing loss (SSNHL).Study Design This was a nonrandomized clinical trial.Setting Tertiary referral center.Patients Forty-four patients, who presented to the outpatient department or the emergency room and those who fulfilled the inclusion criteria, were enrolled in this study. The patients were put into two groups: Group IT—that received intratympanic steroid therapy alone and Group IVIT—that received intratympanic as well as intravenous steroid therapies.Intervention Therapeutic—in the form of IVIT steroid therapy.Main Outcome Measure Impact of the steroid therapy in patients with SSNHL was measured objectively with the help of pure tone audiometry (PTA). The improvement in hearing was assessed in terms of decibels gained after the intervention in both the groups.Results The mean improvement in PTA after 3 months in Group IT was 19.78 (±18.918) dB, whereas the mean improvement after 3 months in Group IVIT was 22.29 (±16.147) dB, statistically showing no significant difference between the groups.Conclusion The authors recommend the use of IT steroid therapy alone in the management of SSNHL.
Keywords: hearing loss; intratympanic steroids; sudden sensorineural hearing loss